Viscosity of liquid Na-K alloy - Koirala, R. P.; Singh, B. P.; Jha, I. S.; Adhikari, D. (BIBECHANA, 2014)
The present work reports a theoretical assessment of the composition dependence of mixing properties of liquid Na-K alloy at 384K at fixed pressure, most likely, at the atmospheric pressure. In this work we have estimated the interaction energy in the alloy at the mentioned temperature on the basis of quasi-chemical approximation for regular alloy and employed it to work out basic thermodynamic properties of mixing such as free energy of mixing, entropy of mixing and enthalpy of mixing as function of composition of the alloy. To understand the dynamic behaviour in the liquid Na-K alloy, we have carried out theoretical investigation of viscosity under consideration of Moelwyn-Hughes equation by using data for enthalpy of mixing obtained from quasi-chemical approximation. Due to scanty of experimental data on viscosity of Na-K alloy at 384K, we have performed computation of viscosity also from Kaptay equation for comparison. The calculations have shown that there is a good match between theoretically computed thermodynamic functions and the available corresponding experimental data. The sets of viscosity values obtained against composition from the two equations show deviations from the ideality and themselves are reasonably comparable to each other. DOI: http://dx.doi.org/10.3126/bibechana.v12i0.11797 BIBECHANA 12 (2015) 128-137